Research on the Ideological and Political Education Model of the Course ‘Energy and Environment’ under the Promotion of Competition - Zhang, Zhiping; Li, Yameng (Journal of Educational Research and Policies, 2025)
Against the backdrop of the national ‘dual carbon’ strategy and the coordinated advancement of ideological and political education within the curriculum, this study explores the integration of the ‘Challenge Cup’ Entrepreneurship Competition as a practical platform to construct an ideological and political teaching model for the course ‘Topics in Energy and Environment’ through case-based instruction. A three-dimensional linkage mechanism—comprising knowledge dissemination, competency development, and value shaping—was established to organically incorporate ideological elements such as ecological civilization and the spirit of serving the nation through science and technology into practical components, including renewable energy technology development and environmental governance planning. The successful implementation of the ‘Soil Guardian’ project, which involves the green conversion of agricultural waste into bio-organic hydrogen fertilizer, significantly enhanced students’ sense of social responsibility and awareness of innovation and entrepreneurship. By analyzing the development process before and after the project won the Challenge Cup Gold Award, the study identifies a replicable and scalable pathway for talent cultivation and curriculum-based ideological and political education.